Integrated analysis of single cell and spatial transcriptomics revealed a metastasis mechanism mediated by fatty acid metabolism in lymph nodes of head and neck cancer - Weng, Jinru; Mao, Jiajie; Li, Yixing; Zhao, Jun; Nong, Xiaolin (Frontiers in Immunology, 2025)
IntroductionHead and neck squamous cell carcinoma (HNSCC) was a common malignant tumor, and its recurrence and metastasis during treatment were the main factors affecting the patient's prognosis. This study aimed to explore the evolutionary mechanisms during HNSCC metastasis.MethodsThis study collected single-cell RNA sequencing (scRNA-seq), spatial transcriptome (ST) data, and fatty acid metabolism-related genes from public databases for pseudo-chronological, differentiation, cell interaction, and pathway analysis. In vivo and in vitro experiments were conducted to study the expression of LGALS1 and its role in HNSCC cells.ResultsThree specific subclusters in the tumor metastasis process were identified, including primary tumors, transitional tumors, and metastatic tumors. During tumor evolution, fatty acid metabolism was upregulated, and active fatty acid metabolism involving LGALS1 was related to HNSCC cell metastasis. Knocking down LGALS1 significantly inhibited the proliferation, migration, and lymph node metastasis ability of HNSCC cells and changed the expressions of E-cadherin, Snail, and PPARγ at the protein level. DiscussionThis study described metabolic changes during HNSCC dissemination and revealed the critical role of metastatic tumors in the mechanism of HNSCC metastasis by regulating fatty acid metabolism.